2010
DOI: 10.1063/1.3506520
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultraviolet emission spectra of Gd and Tb ions

Abstract: Theoretical EUV emission spectra of gadolinium and terbium ions calculated with the Cowan suite of codes and the FAC relativistic code are presented. 4d−4f and 4p−4d transitions give rise to unresolved transition arrays in a range of ions. The effects of configuration interaction are investigated for transitions between singly excited configurations. Optimization of emission at 6.775 nm and 6.515 nm is achieved for Gd and Tb ions respectively by consideration of plasma effects. The resulting synthetic spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…In Fig. 5 the theoretical spectrum is compared with the LPP data of [4] which gives a good fit for an electron temperature of 144 eV and compares well with the earlier FAC code calculation which arrived at an identical value [5]. The laser flux on the target surface was estimated as (5 -8 ) x 10 11 Wcm -2 which yields an average electron temperature is around 135 -180 eV [15].…”
Section: Table I Electronic Configuration Models Used In the Calculasupporting
confidence: 59%
See 3 more Smart Citations
“…In Fig. 5 the theoretical spectrum is compared with the LPP data of [4] which gives a good fit for an electron temperature of 144 eV and compares well with the earlier FAC code calculation which arrived at an identical value [5]. The laser flux on the target surface was estimated as (5 -8 ) x 10 11 Wcm -2 which yields an average electron temperature is around 135 -180 eV [15].…”
Section: Table I Electronic Configuration Models Used In the Calculasupporting
confidence: 59%
“…These studies have shown that plasmas containing tin, where transitions of the type 4p 6 4d n -4p 5 4d n+1 + 4d n-1 4f overlap in ion stages from Sn 9+ -Sn 13+ to form an unresolved transition array (UTA) centered near 13.5 nm are the strongest emitters at this wavelength. To keep pace with Moore's law, research on shorter wavelength EUV sources has already begun [3][4][5][6][7][8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The precise value of x is yet to be determined but will be decided by the source and reflectivity combination that provides the brightest in-band EUV yield and conversion efficiency. Recent theoretical work has proposed 6.76 nm as the optimum choice for the location of the reflectivity peak of EUV optics in a future lithography system based on the fact that the strongest lines observed in this region originate from Ag-and Pd-like ions [1][2][3]. Previous experimental work [4][5][6] has shown the spectral and in-band intensity dependence of Gd plasmas on laser wavelength, intensity and target composition and concentration.…”
mentioning
confidence: 99%